Gamma activity and reactivity in human thalamic local field potentials. - Kempf, F; Brücke, C; Salih, F; Trottenberg, T; Kupsch, A; Schneider, G; Doyle Gaynor, L; Hoffmann, K; Vesper, J; Wöhrle, J; Altenmüller, D; Krauss, J; et al. (2009)
Depth recordings in patients with Parkinson's disease on dopaminergic therapy have revealed a tendency for oscillatory activity in the basal ganglia that is sharply tuned to frequencies of approximately 70 Hz and increases with voluntary movement. It is unclear whether this activity is essentially physiological and whether it might be involved in arousal processes. Here we demonstrate an oscillatory activity with similar spectral characteristics and motor reactivity in the human thalamus. Depth signals were recorded in 29 patients in whom the ventral intermediate or centromedian nucleus were surgically targeted for deep brain stimulation. Thirteen patients with four different pathologies showed sharply tuned activity centred at approximately 70 Hz in spectra of thalamic local field potential (LFP) recordings. This activity was modulated by movement and, critically, varied over the sleep-wake cycle, being suppressed during slow wave sleep and re-emergent during rapid eye movement sleep, which physiologically bears strong similarities with the waking state. It was enhanced by startle-eliciting stimuli, also consistent with modulation by arousal state. The link between this pattern of thalamic activity and that of similar frequency in the basal ganglia was strengthened by the finding that fast thalamic oscillations were lost in untreated parkinsonian patients, paralleling the behaviour of this activity in the basal ganglia. Furthermore, there was sharply tuned coherence between thalamic and pallidal LFP activity at approximately 70 Hz in eight out of the 11 patients in whom globus pallidus and thalamus were simultaneously implanted. Subcortical oscillatory activity at approximately 70 Hz may be involved in movement and arousal.